FLS modeling and using ITS to adopt traffic congestion - AlGhamdi, A.; Eren, Halit; Salem, A. (2013)
Congestion is one of the transportation issues. It increases the fuel consumption with rising of hazardous of roads. Adopting the vehicle desired speed is one of the solutions of the congestion issue and the goal of article. This article has utilized FUZZY logic controller to adopt the congestion. This paper has expressed the controller inputs and output and the relation between them to take decision. It has been explained and novel approach the simulation of congestion system by using close loop system for cluster vehicles. The impact of using ITS in traffic system has been discussed. Comparison between both normal and modern traffic system has been expressed.